Applying social psychology : from problems to solutions - Buunk, Bram; Van Vugt, Mark, 1967- (Los Angeles Sage, 2013)
This is a highly practical text, which can be used by introductory and advanced level students who want to learn how to analyse practical problems and develop solutions based upon social psychological theory and research.
Note continued: Testing the Process Model -- Doing Your Own Research -- 5.The Help Phase: Developing The Intervention -- Introduction -- Preparing Intervention Development -- Developing the Intervention -- Building the Intervention Programme -- Implementation of the Intervention
Previous edition: 2007.
Includes bibliographical references (pages 159-171) and index.
Keywords: Social psychology; Social psychology; Society